Synthesis of Enantiomerically Pure 1′,2′-cis-dideoxy, -dideoxydidehydro, -ribo and -deoxy Carbocyclic Nucleoside Analogues - Weising, Simon; Dekiert, Patrick; Schols, Dominique; Neyts, Johan; Meier, Chris (Synthesis, 2018)
We describe a short and stereospecific synthesis of different series of 1′,2′-cis-disubstituted carbocyclic nucleoside analogues. All-natural nucleobases or their precursors are coupled in a microwave-assisted Mitsunobu-type reaction with enantiomerically pure (1R,2S)-2-(benzyloxymethyl)cyclopent-3-enol. By modifying the cyclopentene scaffold, our synthetic strategy gives access to a series of 1′,2′-cis-disubstituted carbocyclic nucleoside analogues of the dideoxy (dd), dideoxydidehydro (d4) or the ribo series. The ribo series is synthesized in a more convenient way compared to a previous route. The deoxy series of 1′,2′-cis-disubstituted carbocyclic nucleoside analogues is prepared following an earlier reported approach. This synthesis involves the microwave-assisted coupling of (1R,2S,3S)-3-(benzyloxy)-2-[(benzyloxy)methyl]cyclopentan-1-ol with the appropriate nucleobases.
Keywords: carbocycles; Mitsunobu coupling; 1′,2′-cis-substitution; microwave reaction; nucleosides